Caracterização microestrutural de revestimentos de inconel 625 depositados em base de aço microligado APIX 65 pelo processo tig hot wire - Manica, Érik Rogério (2022)
Petroleum industries constantly seek optimization of their materials subject to aggressive media, aiming at reducing possible environmental or economic damages, seeking adaptations that meet this need. An alternative has been the use of the superalloy Inconel 625, as a filler metal for a coating in another less expensive material. The cladding process can cause microstructural rearrangements, seeking to reduce it by opting for the Gas Tungsten Arc Welding process with its Hot wire variation, aiming at a higher rate of material deposition. In order to reduce the consequences caused in the Inconel microstructure, a thermal treatment will be carried out, seeking a reduction of the precipitated phases. This study seeks to analyze and characterize the precipitated phases of an API X65 steel coated with Inconel 625, in its raw melting state and, after a heat treatment, seeking to compare the behavior of the alloy for the two cases portrayed.